Status of the Public Building Sustainability in Lebanon: A Case Study on Fares Library - Folfol, Mahmoud El Cheikh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
In recent years, green buildings have become particularly vital for development of commercial buildings around the world. Some of the benefits of sustainable buildings can be listed as; lowering the usage of water, energy and the overall negative effects to the occupant’s health and the environment. Green building concept is currently may not be the priority for Lebanon, who faced many crises over the last forty years, which resulted in serious damages to its environment, infrastructure and structures. However, the need for re-building Lebanon urges this to be in a sustainable manner. The objective of this research is to find out how ready Lebanon is to implement green building concept, particularly for public buildings. This aim was achieved through; seeking information from authorities, local associations and citizens; a survey distributed to general public, engineers and architects to identify their knowledge and motivation; a case study was conducted on a Library building where some of the green features are present. Furthermore, this building was evaluated using Leadership in Energy and Environmental Design (LEED) certification system to show the benefits of the application of green building concept. It was found that currently Lebanon does not have green building policies in place. But, younger age group seems to have awareness, will to learn, use and apply such concepts. Furthermore, non-government organizations (NGO) appear to have joined forces and giving strong support towards this matter being seriously handled by the authorities. Keywords: green buildings, LEED, library building, build capacity

Öz: Son yıllarda, yeşil bina konsepti, özellikle dünyadaki ticari binaların gelişiminde hayati önem arz etmektedir. Sürdürülebilir binaların faydalarından bazıları şöyle sıralanabilir; su ve enerji kullanımının ve bınada yaşayanların sağlığına ve çevreye olan olumsuz etkilerin genelde azaltılması. Son kırk yıl içerisinde çevre, altyapıya ve binalara ciddi zarar veren birçok krizle karşı karşıya kalmış Lübnan’da, şu anda yeşil bina konsepti öncelik olmayabilir. Fakat Lübnan’ın tekrar yapılaşma gereksinimi bunu sürdürülebilir yapmasına zorlamaktadır. Bu araştırmanın amacı, Lübnan’ın yeşil bina konseptini özellikle kamu binalarında uygulamaya ne kadar hazır olduğunu anlamaktır. Bu amaca şu şekilde ulaşılmıştır; yerek makamlardan, yerel dernekler ve vatandaşlardan bilgi edinerek; sıradan halk, mühendisler ve mimarların konu alakalı bilgi ve motivasyonlarını ölçmek için anket vererek; bazı yeşil özelliklerin bulunduğu bir kütüphane binasına vaka çalışması yaparak. İlaveten, yeşil bina konseptinin faydalarını göstermek için, bu bina Enerji ve Çevre Tasarımında Önderlik (LEED) sertifika programı kullanılarak değerlendirilmiştir. Şu anda Lübnan’da yeşil bina politikası olmadığı ama genç neslin bu konsepti öğrenme, kullanma ve uygulama iradesi ve farkındalığı olduğu görülmüştür. Ayrıca bu konunun devlet tarafından daha ciddi ele alınması için sivil toplum kuruluşlarının güç birleşimi yaptığı ve konuya ciddi destek verdiği gözlemlenmiştir. Keywords: yeşil binalar, LEED, kütüphane binası, çevre
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assist. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering; Green Buildings; Design and Construction; Lebanon; Public Buildings; Sustainability; LEED; library building; build capacity